Activities of the Fifth Abbot of the Aginsky Datsan Galsan-Zhimba Tuguldurov (1817–1872/3) - Sayana B. Bukhogolova; Soelma R. Batomunkueva; Snezhana P. Garmaeva (Монголоведение)
Introduction. The article examines the biography and works of the 5th abbot of Aginsky datsan (Dechen Lhundublin) Galsan Zhimba Tuguldurov. The relevance of the study is determined by importance of the personality of G.-Zh. Tuguldurov. He was one of the most significant Buryat Buddhist leaders of the 19th century. Tuguldurov was one of the bright representatives of the Buryat priesthood, expert in Buddhist philosophy, astrology, medicine and lexicology (he compiled the first Buryat Tibetan-Mongolian dictionary Despite the weight of his multifaceted personality and the presence of works reflecting his activities, the information about the details of G. Tuguldurov's biography and writings continues to remain little known. The purpose of the article is to provide historiographic overview of researches on his biography and creative heritage, introduce some new information into scientific circulation. This information was obtained from archive documents written in Old Mongolic script from the preliminary translation of not studied before biography (namthar) of G.-Zh. Tuguldurov in Tibetan language. The title of the namthar is “The biography of Galsan-Zhimba Balzangpo — the abbot of the datsan Dechen Lhundubling (bde chen lhun grub gling gi khri pa chos rje skal bzang spyin pa dpal bzang po’i rnam thar gyi sa bon bzhugs)”. Materials and methods. The research is based on the works of Russian and Mongolian authors written in different times, archival data from funds of the State Archive of the Republic of Buryatia, Center of Oriental Manuscripts and Xylographs of the Institute for Mongolian, Buddhist and Tibetan studies of the SB RAS and namthar of G.-Zh. Tuguldurov in Tibetan language (archive of Aginsky datsan). The following methods were used: collection, analysis and processing of data, historical-systematic and retrospective analysis. The results of the research helped to restore the chronology of activities of G.-Zh. Tuguldurov. For the first time the biography of G.-Zh. Tuguldurov with additional and clarifying information has been put into scientific circulation. Therefore, the restored biography of G.-Zh. Tuguldurov can make a significant contribution into academic researches, especially into reconstruction of the spread of Buddhism in the region.